2001: tricentenaire de la Grande Paix de Montréal - Beaudoin, Léo (Montréal en tête, 2001)
issued: 2001-24-00
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

The Great Peace of Montreal of 1701: French-Native Diplomacy in the Seventeenth Century - Havard, Gilles (McGill-Queen's University Press, 2001)
Translators: _:n12897
Keywords: Autochtones; Français; Grande Paix de Montréal

From the Ghetto to the Main: the Story of the Jews of Montreal - King, Joe (Montreal Jewish Publications Society, 2001)
Keywords: Juifs

La Grande Paix: chronique d'une saga diplomatique - Beaulieu, Alain; Viau, Roland (Libre Expression et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Iroquois

The Great Peace of Montreal, 1701 - Matusky Gedeon, Julia (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Autochtones; Français; Grande Paix de Montréal

Les lieux de la paix de 1701, et autres considérations sur les campements amérindiens à Montréal - Johnson, Laurence (Recherches amérindiennes au Québec, 2001)
Number: 2
Keywords: Autochtones; Français; Grande Paix de Montréal

Les signatures amérindiennes: essai d’interprétation des traités de paix de Montréal de 1700 et de 1701 - Guillaud, Yann; Delâge, Denis; D'avignon, Mathieu (Recherches amérindiennes au Québec, 2001)
Number: 2
Keywords: Autochtones; Français; Grande Paix de Montréal

The Great Peace: Chronicle of a Diplomatic Saga - Beaulieu, Alain; Viau, Roland (Libre Expression, 2001)
Translators: _:n12489
Keywords: Autochtones; Français; Grande Paix de Montréal

Perceptions linguistiques à Montréal - Laur, Elke (Université de Montréal, 2001)
Keywords: Langue

Memory and Migration: Ethiopian Jews in Montreal - Djerrahian, Gabrielle (Université de Montréal, 2001)
Keywords: Africains; Juifs

Transmission culturelle aux enfants par de jeunes couples immigrants. Montréal, Québec, Sherbrooke - Helly, Denise; Vatz-Laaroussi, Michèle; Rachedi, Lilyane (Immigration et Métropoles, 2001)
Keywords: Enfants

Le mouvement communautaire haïtien de Montréal en tant que mouvement social - Boucard, Alix (Université de Montréal, 2001)
Keywords: Haïtiens

L'identité ethnolinguistique de jeunes adultes issus de couples mixtes francophones/anglophones à Montréal - Hadiri, Myriam (Université de Montréal, 2001)
Keywords: Anglophones; Francophones; Langue

Le jeûne du ramadan en contexte de migration: le cas des immigrants d'origine marocaine à Montréal - Grégoire, Anne-Josée (Université de Montréal, 2001)
Keywords: Maghrébins; Marocains

"Identification des valeurs, des objectifs et des finalités actuels et souhaités de l'éducation chez les musulmans de la région de Montréal" - Aoui, Jamel (Université de Montréal, 2001)
Keywords: Musulmans

Du képi au kippa: implantation des nouvelles politiques de rapprochement du service de police de la Communauté urbaine de Montréal en milieu hassidique - Shamlian, Isabelle (Université du Québec à Montréal, 2001)
Keywords: Hassidim; Juifs; Police

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal: le cas des Français, des Vietnamiens, des Libanais et des Haïtiens - Ndiaye, Sophie (Université du Québec à Montréal, 2001)
Keywords: Français; Haïtiens; Libanais; Vietnamiens

L'expérience de la pratique de la danse salsa des jeunes adultes dans deux discothèques latines de Montréal: une participation à une culture, une rencontre, un rituel - Burelle, Édith (Université du Québec à Montréal, 2001)
Keywords: Danse; Latino-Américains

Les pratiques de gestion dans les PME de la communauté haïtienne de Montréal - Michel, Dicarmel (École des hautes études commerciales de Montréal, 2001)
Keywords: Haïtiens

Toot Sweet: When Jazz Ruled Montreal - Reynolds, Mark (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Musique; Noirs

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

Le Black Theatre Workshop de Montréal: un nouveau bilan - Bayne, Clarence (L'annuaire théâtral, 2001)
issued: 2001-21-00
Keywords: Noirs; Théâtre

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme

Le Montréal juif entre les deux guerres / Tsvishn tsvey velt milhomes - Medresh, Israël (Septentrion, 2001)
Translators: _:n32043
Keywords: Juifs

Groupes, identités et municipalités dans l’histoire de Montréal et de sa région - Linteau, Paul-André (Ministère des Affaires municipales et de la Métropole du Québec, 2001)

La dépression politique des Anglo-Montréalais lors de la crise des années trente - Jedwab, Jack (Bulletin d'histoire politique, 2001)
issued: 2001-24-00
Keywords: Anglophones; Crise

“Le Québec a charge d’âme”: l’Action française de Montréal et les minorités françaises (1917-1928) - Bock, Michel (Revue d'histoire de l'Amérique française, 2001)
En s'appuyant sur l'exemple de la revue mensuelle L'Action française, cet article cherche à circonscrire la place des minorités françaises du Canada dans le nationalisme canadien-français des années 1920, problématique négligée par les historiens. L'auteur démontre que la conception « romantique » qu'avait la revue de la nation canadienne-française faisait des minorités les vestiges ou le prolongement du grand « Empire français d'Amérique », argument qui sera fréquemment utilisé par la rédaction afin de revendiquer le respect de leurs droits scolaires et religieux. Par ailleurs, ce n'est que lorsque considérés en fonction des minorités françaises que quelques-uns des plus importants thèmes du nationalisme canadien-français, comme la mission providentielle du Canada français, trouvent tout leur sens. La nation étant une entité « organique », L'Action française assignait également au Québec un devoir de solidarité nationale envers les minorités aux prises avec les politiquesassimilatrices de la majorité anglo-protestante du pays.
issued: 2001-24-00
Keywords: Action française (L'); Nationalisme

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

The Practice and Meaning of Bonsai, Ikebana, and Tea in Montreal and Abroad: A Case Study of the Processes of Cultural Globalization - Wilson, Hayley (Université Concordia, 2001)
Keywords: Japonais

Les trajectoires des jeunes d'origine haïtienne dans le système québécois de protection de la jeunesse - Bernard, Léonel (Université de Montréal, 2001)
Keywords: Haïtiens

Appréhender la nation, vivre la diaspora regards arméniens - Lenoir-Achdjian, Annick (Université de Montréal, 2001)
Keywords: Arméniens

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens